Pengaruh Budaya Organisasi, Pendidikan Pelatihan Dan Motivasi Terhadap Peningkatan Kinerja Pegawai Di Man Kota Medan - Aida Nurul Fadhilah (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2020)
Organizational culture that already exists in one organization can continue to be maintained and can affect the performance improvement of employees, but in reality the organizational culture in MAN Medan has not been able to improve the performance of employees. In a addition, there is still a lack of training education held for employees that can improve performance and motivation to work. The purpose of research was (1) to determine the influence of cultural organizations to increase the performance employees of MAN in Medan city, (2) to determine the effect of educational training to increase the performance employees of MAN in Medan city, (3) to determine the effect of motivation work employees to increase performance employees of MAN in Medan city, (4) to find out the influence of organizational culture, training education, work motivation to improve employee performance in Medan city. This research is located at MAN Medan city, in MAN 1 with the address at Jalan Willem Iskandar No. 7B, MAN 2 Model Medan the address at Willem Iskandar No. 7A, and MAN 3 Medan Which is located on jalan Patumbak Defense No.99. This research is a quantitative study with total project sample of 55 people is determined by using the method of population target that all populations used as respondents. Then sample a number of populations that exist. Research consisting of four variables was measured using a questionnaire, namely by compiling a questionnaire and then distributed to respondents to be answered. Each variable is determined in several indicators whose selection is based on a theoretical study. Results of the study showed that (1) there is influence of positive and significant between cultural organizations to increase the performance of employees. Cultural organizations give effect to increase the performance of employees amounted to 8,3% and the remaining 91,7% is determined by other factors, (2) there is a positive and significant effect between training educationon improving employee performance. Training education has an influence on improving employee performance. Training education has an effect on improving employee performance by 14,3% and the remaining 85,7% is determined by other factors. (3) there is a positive and significant influence between work motivation on improving employee performance. Motivation gives an influence on improving employee performance by 12% and the remaining 87,8% is determined by other factors, (4) there is a positive and significant influence between organizational culture, training education, work motivation on improving employee performance. Organizational culture, training education, work motivation have an effect on improving employee performance by 19,1% and the remaining 80,9% is determined by other factors